Green emission from semipolar InGaN quantum wells grown on low‐defect (112¯2) GaN templates fabricated on patterned r‐sapphire. Issue 1 (19th November 2015) - de Mierry, P.; Kappei, L.; Tendille, F.; Vennéguès, P.; Leroux, M.; Zuniga‐Perez, J.
Abstract : In this article, InGaN/GaN multiple quantum wells (MQWs) grown on low‐defect ( 11 2 ¯ 2 ) GaN templates are investigated by photoluminescence (PL), cathodoluminescence (CL), and transmission electron microscopy (TEM). The emission wavelength is tuned from 450 nm (blue) to 550 nm (green) by varying the TMGa flux in the QWs, while keeping the temperature constant. The In content in the QWs is found to increase with increasing TMGa flux. CL measurements show that the first QW and often the second one emit systematically at wavelengths shorter than the following QWs, while TEM measurements indicate that these first QWs are slightly thinner and display less In content than the rest of the stack. Both observations might be explained by considering that these first QWs grow under larger compressive strain than the subsequent QWs. Furthermore, since TEM shows that misfit dislocations oriented along the [ 1 1 ¯ 00 ] direction are mainly located at the lower MQW stack interface, i.e., between the first QW and the underlying template, the correlation between TEM and CL points toward a plastic relaxation occurring after the stacking of a sufficiently large number of QWs.